2021
DOI: 10.7324/jhsr.2021.622
|View full text |Cite
|
Sign up to set email alerts
|

Practice of Breast Self-Examination among Female Students of Chukwuemeka Odumegwu Ojukwu University, Awka

Abstract: ABSTRACT: Background: Breast self examination (BSE) is a fairly reliable procedure for early detection of breast cancer especially in limited resource countries where access to and availability of mammography is inadequate. BSE helps women to be familiar with their breasts and increases awareness of breast cancer and breast cancer screening modalities like Clinical breast examination (CBE) and Mammography. This study aims at testing the knowledge base of our female tertiary students on breast cancer in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Three (3) (Ogun, 2019;Hanson et al, 2019) reported on knowledge, practice and perception while Sani and Yau (2018) reported knowledge and practice alone. Finally, Akpanekpo (2019), Olaogun et al (2017) and Madubogwu (2021) reported on awareness, attitude and practice.…”
Section: Study Findingsmentioning
confidence: 99%
See 2 more Smart Citations
“…Three (3) (Ogun, 2019;Hanson et al, 2019) reported on knowledge, practice and perception while Sani and Yau (2018) reported knowledge and practice alone. Finally, Akpanekpo (2019), Olaogun et al (2017) and Madubogwu (2021) reported on awareness, attitude and practice.…”
Section: Study Findingsmentioning
confidence: 99%
“…The two (2) experimental studies among them (Ibitoye & Thupayegaletshwene Game, 2019;Ogun, 2019) recorded a very low knowledge among the participants before intervention, which increases above average after intervention. The remaining three articles by Olaogun (2017), Madubogwu (2021) and Akpanekpo (2017) did not report on knowledge but on awareness. The seven studies that reported knowledge of BSE above average were conducted among female nurses (Yakubu et al, 2014), community women (Iwuoha et al, 2021), secondary school girls (Alabi et al, 2018;Usman et al, 2020) and the remaining three among female undergraduates (Casmir et al, 2015;Lafiaji-Okuneye et al, 2022;Ossai et al, 2019).…”
Section: Knowledge Of Women On Bsementioning
confidence: 99%
See 1 more Smart Citation